"Managing the Wait": Parents' Experiences in Accessing Diagnostic and Treatment Services for Children and Adolescents Diagnosed With Autism Spectrum Disorder. (January 2020) - Smith-Young, Joanne; Chafe, Roger; Audas, Rick
Background: Parents of children and adolescents diagnosed with autism spectrum disorder (ASD) report delays in accessing timely diagnostic and treatment services for their children. Research has generally focused on parents' experiences in caring for a child diagnosed with ASD. This study describes the process of how parents access ASD services for their children and adolescents. Method: This study used a qualitative research design that was informed by grounded theory methodology. We used constant comparative analysis to develop a process model and a core concept. Results: Seventeen parents of children and adolescents diagnosed with ASD were interviewed. Our process model included 3 main phases: Watchful waiting (noticing suspected behaviors, and searching for assessment and diagnosis); Informed waiting (receiving the diagnosis, facing challenges in accessing treatment services, and realizing the impact of an ASD diagnosis); and Contemplative waiting (pondering the future, reflecting on the past, and making recommendations). "Managing the Wait" was identified as the core category central to parents' experience of this process. This process was found to be impacted by socioeconomic status, parents' skills and capacity to advocate on their child's behalf, and severity of their child's ASD. Conclusions: Our findings illustrate the many barriers families face during their journey in accessing ASD services. Our results illustrate the need to address wait times for services, and provide education and support services for parents as a means of improving their self-advocacy skills, especially for parents of children and adolescents with severe disability.